2000
DOI: 10.1016/s0002-9440(10)64999-1
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Squamous Cell Carcinoma to Adenocarcinoma in Adenosquamous Carcinoma of the Lung

Abstract: The heterogeneity of tumor cells is frequently observed in lung cancer, but the clonality of these cells has not yet been established. The distinct components of 12 lung adenosquamous carcinomas were compared by genetic alterations of p53 and K-ras, chromosomal abnormalities at 9p21 and 9q31-32, and immunohistochemical reactions. The immunoreactivity of p53 was consistent in both adenocarcinomatous and squamous cell carcinomatous components as well as in the transitional areas, retaining the morphological char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…Interestingly, the two components of the adenosquamous tumors appear to be correlated, suggesting that the expression of thymidylate synthase is driven more by other tumor determinants than histological pattern. This is also consistent with the Kanazawa study 26 of 12 adenosquamous tumors, in which they sought to determine polyclonality versus monoclonality of these tumors. With immunohistochemistry, they found higher expression levels of squamous cell carcinoma-related antigen and lower expression of Mucin-1 in the glandular components than usual adenocarcinomas of the lung.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, the two components of the adenosquamous tumors appear to be correlated, suggesting that the expression of thymidylate synthase is driven more by other tumor determinants than histological pattern. This is also consistent with the Kanazawa study 26 of 12 adenosquamous tumors, in which they sought to determine polyclonality versus monoclonality of these tumors. With immunohistochemistry, they found higher expression levels of squamous cell carcinoma-related antigen and lower expression of Mucin-1 in the glandular components than usual adenocarcinomas of the lung.…”
Section: Discussionsupporting
confidence: 78%
“…[10][11][12] In our study, we investigated the molecular features of adenosquamous carcinoma, a typical heterogeneous tumor of the lung.…”
Section: Dear Sirmentioning
confidence: 99%
“…3 Information on genetic alterations is also limited; only TP53, K-ras mutation and loss of heterozygosity at several loci have been reported in a limited number of adenosquamous carcinomas. [10][11][12] In our study, we investigated the molecular features of adenosquamous carcinoma, a typical heterogeneous tumor of the lung.…”
Section: Dear Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, dierent animals or dierent breasts in the same animal developed independently invasive tumors with a predominating solid, nodular form that possibly evolved into a few variants, including a pattern of adenoacanthomatous metaplasia. Although adenosquamous carcinomas developing in the breast or in other organs are rarely observed in humans (see, for example, Denley et al, 2000), it is interesting to note that independent molecular analyses of lung tumors have suggested that the squamous and adenocarcinomatous components had originated from the same cell (Niho et al, 1999;Kanazawa et al, 2000).…”
Section: Tumor Pathogenesis In the Absence Of Brca2mentioning
confidence: 99%